Media Pembelajaran Interaktif Mengenal Ilmu Tajwid Di 10 Ayat Pertama Pada Surah Al-Kahfi Berbasis Android - Khairatul Janah; Haida Dafitri; Nur Wulan (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2021)
Along with the rapid development of technology and information, especially in the field of education, one of which is by utilizing multimedia as a learning medium. The source of the material for recitation of tajwid which is still presented in conventional form like ordinary textbooks, of course, makes tajwid less interesting to learn and also not all children immediately understand it. It takes teaching staff who can teach recitation material in an interesting way. Of course, this cannot be done anymore due to the current pandemic situation to reduce crowds. An example of technology that can be used is an Android-based Smartphone. One of the lessons that can be developed through Smartphones is an interactive learning media to know the science of recitation based on Android. Interactive learning media that was built with the aim of being able to be implemented for children to recognize the science of recitation in the first 10 verses of Surah Al-Kahf. With the hope that interactive learning media can help children learn Tajweed law easily.  Keywords : Android, Adobe Animated CC, Science Tajwid, Surah Al-Kahfi.